The Correlation Between Students’ Ability In Identifying Nouns And Adjectives To Analyzing Compound Noun And Compound Adjectives Of TBI Students IAIN Padangsidimpuan - Rayendriani Fahmei Lubis, Fitriadi Lubis, Fitri Rayani Srg, (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
This research is designed by quantitative aproach and correlational research. In this research, participants were students in third semester of english Educational Departement at Tarbiyah and pedagoy Faculty Institute of Islamic Studies Padangsidimpuan. The participant of research is TBI-1. They are 30 students. The instrument use in this research is a test. Then, the test analyzed by applying product moment formula to test hyphotheses. The calculating of product moment by getting correlation coefficients rxy = 0.53 The significant correlation level was done by locking rtabel (rt) on significant level 5% was 0.361 and on significant level 1% was 0.463. The hypnothesis in this research was accepted namely rcount rtabel. It meant there was significant correlation between students’ ability in identifying noun and adjective to students’ ability in analyzing compound noun and compoun adjective